2015
DOI: 10.1159/000438761
|View full text |Cite
|
Sign up to set email alerts
|

RbAp48 Is Critical for the Proliferation of Hypopharyngeal Carcinoma

Abstract: Background: Emerging evidence has indicated the significance of RbAp48 in tumorigenesis. Although many genetic and epigenetic factors have been found to be involved in the pathogenesis of hypopharyngeal carcinoma, the effect of RbAp48 in hypopharyngeal carcinoma is still unclear. Methods: A stable cell line overexpressing RbAp48 was generated in FaDu cells. Cell proliferation and colony formation were detected using FaDu-RbAp48 cells. Next we utilized nude mouse xenografts to determine the role of RbAp48. Flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…They are generally diagnosed at an advanced stage and have a bad prognosis [1,2]. These cancers arise in the upper aerodigestive tract and hypopharyngeal and upper esophageal regions, and surgical ablation of advanced tumors may result in a large surgical defect.…”
Section: Introductionmentioning
confidence: 99%
“…They are generally diagnosed at an advanced stage and have a bad prognosis [1,2]. These cancers arise in the upper aerodigestive tract and hypopharyngeal and upper esophageal regions, and surgical ablation of advanced tumors may result in a large surgical defect.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that RBBP4 is upregulated in ESCC and promotes the epithelial-mesenchymal transition (EMT) process (131). By contrast, Bai et al (132) demonstrated that in hypopharyngeal carcinoma, a distinct squamous cell carcinoma impacting the upper aerodigestive tract, RBBP4 overexpression curtails proliferation, colony formation and tumorigenesis in the FaDu hypopharyngeal carcinoma cell line. The role of RBBP4 in hypopharyngeal carcinoma growth appears linked to its modulation of tumor suppressors.…”
Section: Hematological (Blood and Bone Marrow) System Diseases Acute ...mentioning
confidence: 99%